The impact of technological innovation and public‐private partnership investment on sustainable environment in China: Consumption‐based carbon emissions analysis. (22nd June 2020) - Khan, Zeeshan; Ali, Muhsin; Kirikkaleli, Dervis; Wahab, Salman; Jiao, Zhilun
Abstract: The present study investigates the effect of public‐private partnership investment in energy and technological innovation on consumption‐based carbon emissions for China from 1990Q1 ‐2017Q2 . This study employs generalized least square (GLS) based unit root test, Maki cointegration test, fully modified ordinary least square (FMOLS), dynamic ordinary least square (DOLS), canonical cointegration regression (CCR) and frequency domain causality test. The finding of this study shows that (a) the cointegrating relationship among public‐private partnership investment in energy, technological innovation, renewable energy consumption, exports, imports, and consumption‐based carbon emissions is proved; (b) exports, renewable energy consumption and technological innovation are helpful to lower consumption‐based carbon emissions; (c) both public‐private partnership investment in energy, GDP and imports leads to increased consumption‐based carbon emissions; (d) in the long term, public‐private partnership investment and technological innovation cause consumption‐based carbon emissions in China. This study recommends technological innovation for the cleaner production process and public‐private partnership investment in renewable energy.